2011
DOI: 10.1093/jjco/hyr173
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity Profile of Human Papillomavirus-16/18 AS04 Adjuvant Cervical Cancer Vaccine: A Randomized Controlled Trial in Healthy Adolescent Girls of Bangladesh

Abstract: AimBangladesh has the highest level of incidence and mortality rates due to cervical cancer among women. The prevalence of cervical cancer in Bangladeshi women is 25–30/100 000. Human papillomavirus is an important cause of cervical cancer. The study was conducted to assess the immunogenicity and safety profile of human papillomavirus-16/18 AS04-adjuvanted cervical cancer vaccines in healthy Bangladeshi girls aged 9–13 years.ProcedureThis was a randomized (3:1) controlled trial with two parallel groups, the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…Most of the studies (N = 7) provided their clinical trial registration numbers (31)(32)(33)(34)(35)38,39). In addition, almost all studies (N = 9) included only women (30)(31)(32)(33)(34)(35)(36)38,39). In general, the age of participants in the studies varied considerably from 9 to 45 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the studies (N = 7) provided their clinical trial registration numbers (31)(32)(33)(34)(35)38,39). In addition, almost all studies (N = 9) included only women (30)(31)(32)(33)(34)(35)(36)38,39). In general, the age of participants in the studies varied considerably from 9 to 45 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The bivalent vaccine (Cervarix), containing VLP antigens for HPV types 16 and 18, was licensed for preventing precancerous cervical lesions and cervical cancer [1,2] in September 2007. In February 2015, the nine-valent HPV vaccine (Gardasil 9), containing four HPV VLPs that are in the qHPV (6,11,16, and 18) plus five additional HPV VLP types (31,33, 45, 52, and 58), was recommended for approval in Europe for use in the prevention of cervical, vulvar, vaginal, and anal cancer, genital warts and precancerous lesions of the cervix, vulva, vagina, and anus [3]. Neither of the vaccines protect against HPV types for which the individual is already seropositive at the time of vaccination [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most common AEFI was injectionrelated local reaction [8,9]. Fever, nausea, vomiting, dizziness, myalgia and diarrhoea were the most commonly reported systemic symptoms [8,10,11]. Severe AEFIs, such as severe headache with hypertension and bronchospasm were described in 0.5% [8].…”
Section: Introductionmentioning
confidence: 99%
“…4 In another study that led to approval of Gardasil and Cervarix, these vaccines were found t o p r ovide nearly 1 0 0% p r otection against persistent cervical infections with HPV types 16 and 18 and t he cervical cell changes t hat these persistent infections can cause. 21 A clinical trial of Gardasil in men indicated that it can prevent anal cell changes caused by persistent infection and genital warts. 22 Although these two vaccines give 5-year protection, long-term studies of vaccine efficacy t hat are still in p r ogress will help scientists b e tter understand t he total duration of protection.…”
Section: Vaccine Efficacymentioning
confidence: 99%